Development of Geographic Information Systems and their use in National Libraries of Russia - Kotelnikova, Natalya; Kildyushevskaya, Ludmila (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2005)
By the end of the 20th century cartography has amassed a vast array of information on major aspects of existence, interaction and the functioning of nature and society owing to vigorous automation and computerisation. These are applied for the purpose of creating geographic information systems (GIS). The main function of geographic information systems is the storage and use of computer (electronic) maps and atlases. Geographic information systems differ from each other in their territorial levels (global, national, regional, municipal and others) and by their subjects (land, cadastre, ecological, sea and other maps). The geographic information system, ‘Black Sea’ is cited as an example. This is an information-based project compiled with a view to taking decisions on the protection of the resources of the basin of the Black Sea. The Black Sea GIS was developed for use by governments, scientists, the general public, NGOs and the media for the following purposes: · planning for marine environment activities and impacts on a regional scale; · public awareness through training, education, workshops, lectures and media; · scientific analysis, modelling, ecological impact assessment, science planning. The main GIS components are designed to perform the following functions: · data input; · data storage and database management; · data analysis and processing; · interaction with the user (graphical/map editing); and · data output and presentation (plotting).